2009
DOI: 10.1051/0004-6361/200811528
|View full text |Cite
|
Sign up to set email alerts
|

Is β Pictoris b the transiting planet of November 1981?

Abstract: In 1981, β Pictoris showed strong and rapid photometric variations that were attributed to the transit of a giant comet or a planet orbiting at several AUs. Recently, a candidate planet has been identified by imagery in the circumstellar disk of β Pictoris. This planet, named β Pic b, is observed at a projected distance of 8 AU from the central star. It is therefore a plausible candidate for the photometric event observed in 1981. The coincidence of the observed position of the planet in November 2003 and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…In addition, a 10 M Jup planet at 10 au has been inferred as the cause of a warp in the disc (Mouillet et al 1997) that reaches a peak near the same location as the parent belt (Heap et al 2000). This proposed companion has recently been imaged (Lagrange et al 2009b), though confirmation with second epoch observations is needed (Lagrange et al 2009a; Lecavelier Des Etangs & Vidal‐Madjar 2009). Finally, Telesco et al (2005) find an apparent clump of small grains in the south‐west wing of the disc at 50 au.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, a 10 M Jup planet at 10 au has been inferred as the cause of a warp in the disc (Mouillet et al 1997) that reaches a peak near the same location as the parent belt (Heap et al 2000). This proposed companion has recently been imaged (Lagrange et al 2009b), though confirmation with second epoch observations is needed (Lagrange et al 2009a; Lecavelier Des Etangs & Vidal‐Madjar 2009). Finally, Telesco et al (2005) find an apparent clump of small grains in the south‐west wing of the disc at 50 au.…”
Section: Discussionmentioning
confidence: 94%
“…Lecavelier des Etangs et al (1997) showed that a planet with 2-4 times the radius of Jupiter, orbiting at ∼9 AU at most could well be responsible for the photometric variations they reported. Lecavelier des Etangs & Vidal-Madjar (2009) [7.6-8.7] AU. They also predicted that if the planet detected in 2003 on the NE side of the disk matched the one they predicted, it should reappear on the SW side in 2009 roughly where it was reobserved.…”
Section: Transiting Eventmentioning
confidence: 99%
“…Finally, it has been suggested that the 2003 candidate planet could have been responsible for a peculiar photometric variability event observed in 1981, when transiting in front of the star (27). The 2009 data are compatible with this possibility [see also (19)], however, only for a small range of planet orbital parameters.…”
mentioning
confidence: 99%